2021
DOI: 10.1007/s00264-021-05080-8
|View full text |Cite
|
Sign up to set email alerts
|

Proximal femoral reconstruction with modular megaprostheses in non-oncological patients

Abstract: Introduction Multiple revision hip arthroplasties and critical trauma might cause severe bone loss that requires proximal femoral replacement (PFR). The aim of this retrospective study was to analyse complication- and revision-free survivals of patients who received modular megaprostheses in an attempt to reconstruct massive non-neoplastic bone defects of the proximal femur. Questions/purposes (1) What were general complication rates and revision-free survivals followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Artificial ligaments can also be used to reduce the dislocation rate [ 89 ]. Post-operative care is of paramount importance with immobilization of the limb operated on in abduction for various post-operative durations, and protected weight-bearing thereafter [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Artificial ligaments can also be used to reduce the dislocation rate [ 89 ]. Post-operative care is of paramount importance with immobilization of the limb operated on in abduction for various post-operative durations, and protected weight-bearing thereafter [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Döring et al reported a mixed case series of MPs implanted for non-oncological purposes. Eleven PJIs were treated for PJI, and coating use was not mentioned: 3 were lost at follow up and 5 had a recurrence [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the case of very large defects, custom-made (CM) 3D-printed prosthesis and proximal femur (PF) megaprosthesis (MP) have been proposed [16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%